Emerging Environmental Justice Issues in Nuclear Power and Radioactive Contamination - Kyne, Dean; Bolin, Bob (International journal of environmental research and public health, 2016)
Nuclear hazards, linked to both U.S. weapons programs and civilian nuclear power, pose substantial environment justice issues. Nuclear power plant (NPP) reactors produce low-level ionizing radiation, high level nuclear waste, and are subject to catastrophic contamination events. Justice concerns include plant locations and the large potentially exposed populations, as well as issues in siting, nuclear safety, and barriers to public participation. Other justice issues relate to extensive contamination in the U.S. nuclear weapons complex, and the mining and processing industries that have supported it. To approach the topic, first we discuss distributional justice issues of NPP sites in the U.S. and related procedural injustices in siting, operation, and emergency preparedness. Then we discuss justice concerns involving the U.S. nuclear weapons complex and the ways that uranium mining, processing, and weapons development have affected those living downwind, including a substantial American Indian population. Next we examine the problem of high-level nuclear waste and the risk implications of the lack of secure long-term storage. The handling and deposition of toxic nuclear wastes pose new transgenerational justice issues of unprecedented duration, in comparison to any other industry. Finally, we discuss the persistent risks of nuclear technologies and renewable energy alternatives.